2019
DOI: 10.1037/edu0000329
|View full text |Cite
|
Sign up to set email alerts
|

Refutation texts compensate for detrimental effects of misconceptions on comprehension and metacomprehension accuracy and support transfer.

Abstract: Science Society in London, UK (2017, July) and have been published in a proceedings paper (Prinz, Golke, & Wittwer, 2017). The proceedings paper and this manuscript overlap in some of the data concerning comprehension and metacomprehension accuracy of the statistics text. However, the proceedings paper only presented results of a subsample and included no thinkaloud data and no analyses on transfer. The authors declare that they have no conflict of interest. This study was funded by the Bundesministerium für B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 76 publications
5
40
2
3
Order By: Relevance
“…B. Prinz et al 2019). Beispielsweise könnten Schülerinnen und Schüler eine Erklärung lesen und unter dem Eindruck, die Erklärung verstanden zu haben, keine weiteren Lernaktivitäten unternehmen.…”
Section: Wie Kann Die Weiterverarbeitung Von Lerninhalten Gezielt Gefunclassified
“…B. Prinz et al 2019). Beispielsweise könnten Schülerinnen und Schüler eine Erklärung lesen und unter dem Eindruck, die Erklärung verstanden zu haben, keine weiteren Lernaktivitäten unternehmen.…”
Section: Wie Kann Die Weiterverarbeitung Von Lerninhalten Gezielt Gefunclassified
“…(2017), students were instructed to judge statements that included common misconceptions as correct or incorrect, followed by a feedback phase: refutation texts stated and dispelled the misconceptions, and either included an explanation of the refutation (i.e., elaborate feedback) or not (i.e., corrective feedback). Results showed that—in the long run-learners were more likely to correct misconceptions when an explanation was provided why a statement was incorrect, compared to when only a refutation and the correct answer was given, and this even after longer retention intervals (Ecker et al., 2020; Rich et al., 2017). Similarly, recent studies using more educationally relevant materials (e.g., Prinz et al., 2019) also demonstrated beneficial effects of refutation (over standard) texts on statistics in terms of a decreased rate of misconceptions and, associated with it, an enhanced textual comprehension and metacomprehension accuracy (i.e., ability to predict future comprehension performance).…”
Section: The Importance Of Feedback For Successful Learningmentioning
confidence: 97%
“…The potential benefit of elaborate (over corrective) feedback has also been investigated in other research domains, such as knowledge revision and text comprehension: different types of refutation texts are typically provided to correct false beliefs and to enhance the comprehension and application of knowledge statements, concepts, or mental models (e.g., Ecker et al., 2020; Prinz et al., 2019; Rich et al., 2017). For example, in the study by Rich et al.…”
Section: The Importance Of Feedback For Successful Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of the refutation encourages active contrasting with the correct scientific information and explanation and thereby increases the chance that misconceptions will be rejected and the correct information internalised . Refutation texts have also been observed to make students interact more actively with the learning material, to improve the accuracy of meta‐comprehension (ie learners’ self‐assessments of their understanding), and to increase the transfer of newly gained knowledge to other contexts …”
mentioning
confidence: 99%